LO01: What presenting features predict obstetrical outcomes in women who present to the emergency department with early pregnancy bleeding?. (May 2020) - Burgoyne, M.; Clouston, R.; Banerjee, A.; Fraser, J.; Atkinson, P.
Abstract : Introduction: Vaginal bleeding in early pregnancy is a common emergency department (ED) presentation, with many of these episodes resulting in poor obstetrical outcome. These outcomes have been extensively studied, but there have been few evaluations of what variables are associated predictors. This study aimed to identify predictors of less than optimal obstetrical outcomes for women who present to the ED with early pregnancy bleeding. Methods: A regional centre health records review included pregnant females who presented to the ED with vaginal bleeding at <20 weeks gestation. This study investigated differences in presenting features between groups with subsequent optimal outcomes (OO; defined as a full-term live birth >37 weeks) and less than optimal outcomes (LOO; defined as a miscarriage, stillbirth or pre-term live birth). Predictor variables included: maternal age, gestational age at presentation, number of return ED visits, socioeconomic status (SES), gravida-para-abortus status, Rh status, Hgb level and presence of cramping. Rates and results of point of care ultrasound (PoCUS) and ultrasound (US) by radiology were also considered. Results: Records for 422 patients from Jan 2017 to Nov 2018 were screened and 180 patients were included. Overall, 58.3% of study participants had a LOO. The only strong predictor of outcome was seeing an Intra-Uterine Pregnancy (IUP) with Fetal Heart Beat (FHB) on US; OO rate 74.3% (95% CI 59.8-88.7; p < 0.01). Cramping (with bleeding) trended towards a higher rate of LOO (62.7%, 95% CI 54.2-71.1; p = 0.07). SES was not a reliable predictor of LOO, with similar clinical outcome rates above and below the poverty line (57.5% [95% CI 46.7-68.3] vs 59% [95% CI 49.3-68.6] LOO). For anemic patients, the non-live birth rate was 100%, but the number with this variable was small (n = 5). Return visits (58.3%, 95% CI 42.2-74.4), previous abortion (58.8%, 95% CI 49.7-67.8), no living children (60.2%, 95% CI 50.7-69.6) and past pregnancy (55.9%, 95% CI 46.6-65.1) were not associated with higher rates of LOO. Conclusion: Identification of a live IUP, anemia, and cramping have potential as predictors of obstetrical outcome in early pregnancy bleeding. This information may provide better guidance for clinical practice and investigations in the emergency department and the predictive value of these variables support more appropriate counseling to this patient population.